Association between advanced lung cancer inflammation index and all-cause and cause-specific mortality among asthma patients: a cohort study - Tian, Tu-Lei; Qu, Xiang-Kun; Zhang, Hong-Bo; Wang, Cun-Cun; Yuan, Qing-Qing; Xia, Jing; Cao, Li-Fang; Liu, Kui (Frontiers in Nutrition, 2025)
BackgroundThe advanced lung cancer inflammation index (ALI), which reflects both inflammation and nutritional status, has an uncertain role in predicting outcomes for asthma patients. This study aimed to evaluate the association between ALI and mortality from all causes, as well as specific causes including cardiovascular disease (CVD) and cancer-related mortality, among individuals with asthma.MethodsWe analyzed data from 4,829 asthma patients who participated in the U.S. National Health and Nutrition Examination Survey (NHANES) from 1999 to 2018. Cox proportional hazards models were used to assess the relationship between ALI and both all-cause and cause-specific mortality, adjusting for demographic and clinical variables. Additionally, restricted cubic spline models were applied to explore potential nonlinear trends, while segmented Cox models were used to identify threshold effects. A competing risk model further examined the independent association of ALI with CVD mortality.ResultsOver a median follow-up of 7.83 years, a total of 582 deaths from all causes, 151 cardiovascular-related deaths, and 125 cancer-related deaths were recorded. An L-shaped association was observed between ALI and both all-cause and CVD mortality, with thresholds identified at 82.02 for all-cause mortality and 58.40 for CVD mortality. Compared to the lowest quartile of ALI (Q1), patients in the highest quartile (Q4) had a 49% lower risk of all-cause mortality (hazard ratio [HR] 0.51, 95% confidence interval [CI] 0.40–0.66) and a 51% reduction in CVD mortality (HR 0.49, 95% CI 0.29–0.83). This protective effect was further confirmed by the competing risk model. No significant association between ALI and cancer mortality was observed (HR 1.01, 95% CI 0.98–1.03).ConclusionALI was significantly and inversely associated with all-cause and CVD mortality in asthma patients, particularly when ALI values were below 82.02 and 58.40, respectively, where the risk of mortality was substantially lower. These findings suggest that ALI may have clinical utility in assessing prognosis for asthma patients, especially in terms of cardiovascular risk evaluation.